Cutaneous metastatic breast carcinoma with clear cell features. (14th May 2013) - Shinohara, Michi M.; Tozbikian, Gary; Wolfe, Jonathan T.; Shin, Sandra J.; Mies, Carolyn; Elenitsas, Rosalie
<x xml:space="preserve">Abstract</x> Breast carcinoma remains one of the most common sources of skin metastases in women. Cutaneous breast carcinoma metastases have variable clinical and histopathologic presentations that can make diagnosis challenging. We report a unique case of metastatic breast carcinoma with prominent clear cell features, thus mimicking a xanthomatous process. Dermatopathologists should be aware of this entity given its resemblance to other clear cell infiltrates and neoplasms.